2021
DOI: 10.3389/fimmu.2021.744206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Corticosteroid Use on Reactogenicity and Immunogenicity of the First Dose of ChAdOx1 nCoV-19 Vaccine

Abstract: The effects of corticosteroid use on the reactogenicity and immunogenicity of ChAdOx1 nCoV-19 (ChAd) vaccine were evaluated. Healthcare workers (HCWs) who took low-dose corticosteroid agents around the time of the first dose of ChAd (ChAdPd group) were recruited and the reactogenicity and immunogenicity were compared with those of ChAd (ChAd group) and BNT162b2 vaccination (BNT group) of HCWs without corticosteroid exposure. The immunogenicity was measured three weeks after vaccination using quantitative anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 22 publications
0
40
2
1
Order By: Relevance
“…It has been shown that cellular immunity was detectable at 8 months after two doses of BNT162b2, although antibody levels declined significantly ( 20 ). A study investigating the immunogenicity of 23 healthcare workers after the first dose of BNT162b2 or ChAdOx1 nCov-19 presented 67.7% positivity determined using Covi-FERON IGRA ( 21 ). The median values for BNT162b2 and ChAdOx1 nCov-19 were 1.656 and 0.978 IU/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that cellular immunity was detectable at 8 months after two doses of BNT162b2, although antibody levels declined significantly ( 20 ). A study investigating the immunogenicity of 23 healthcare workers after the first dose of BNT162b2 or ChAdOx1 nCov-19 presented 67.7% positivity determined using Covi-FERON IGRA ( 21 ). The median values for BNT162b2 and ChAdOx1 nCov-19 were 1.656 and 0.978 IU/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Covi-FERON ELISA kit (SD Biosensor, Suwon, Korea) was used to detect cell-mediated immune responses to SARS-CoV-2 antigens by measuring IFN-γ secreted by T cells in response to the SARS-CoV-2 antigen ( 21 ). Blood samples collected in heparinized tubes were aliquoted (in 1 mL aliquots) into five tubes for Nil, Mitogen, original spike protein (SP1) antigen, variant spike protein antigen (SP2), and nucleocapsid protein (NP) antigens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that the duration of tocilizumab administration did not impact the response to the vaccine. Also, another recent study showed that although short-term corticosteroid therapy reduces reactogenicity of the first dose of ChAdOx1 nCoV-19, it does not weaken its immunogenicity [ 67 ]. On the other hand, a preliminary report (preprint) shows that methotrexate might hamper humoral and cellular immune response to COVID-19 mRNA vaccines [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Cell-mediated immunity was evaluated by measuring interferon-gamma (IFN-γ) secreted by T-cells in response to SARS-CoV-2-specific antigens using a SARS-CoV-2-specific IFN-γ release assay (IGRA) kit with enzyme-linked immunosorbent assay (ELISA) (Covi-FERON ELISA; SD Biosensor, Suwon, Republic of Korea). 18 The test kit consists of nil, SARS-CoV-2 spike protein antigen (Sp)1, Sp2, mitogen tubes, and IFN-γ ELISA. The Sp1 tube contained spike protein antigens derived from the original SASR-CoV-2 strain and its alpha variant, and the Sp2 tube contained those derived from the beta and gamma variants.…”
Section: Methodsmentioning
confidence: 99%